DETERMINATION OF GENETIC DIVERSITY IN SOME LOCAL ALFALFA (Medicago sativa L.) ECOTYPES USING SSR MARKERS - M. M. Ertus; S. Sensoy (Journal of Animal and Plant Sciences, 2020)
In this study, the genetic diversity and relationships were examined by using SSR markers among six local alfalfa (Medicago sativa L.) ecotypes grown in Eastern Anatolian Region of Turkey. Eleven SSR primers produced 111 polymorphic bands in 90 alfalfa genotypes (15 genotypes from each ecotypes). The maximum (15) and minimum (5) allele numbers were obtained from the primers AFcat32 and AFct11, respectively. The polymorphism rate among the ecotypes ranged from 54.55% to 74.03%. According to the similarity coefficient matrix used to determine the degree of relationship, the closest similarity (0.68) was determined between the ecotypes Catak and Ercis, but the most distant one (0.37) was determined between the ecotypes Gürpınar and Muradiye. From the ecotypes, the genotypes closest to each other (0.88) were found to be in the population of Gurpinar, but the genotypes farthest to each other (0.41) were found to be in the population of Ercis. Based on Nei genetic diversity, the highest genetic diversity was found in the population of Ercis, while the lowest one was obtained in the population of Gurpinar. Moreover, no very closely related genotypes were detected in the studied ecotypes having high genetic diversity.
Keywords: Alfalfa; Medicago sativa; SSR; genetic variation